Tax Planning Analysis: Impact of Institutional, Concentrated and Foreign Ownership - Nurlis, Nurlis; Tarmidi, Deden; Handayani, Tri; Romadona, Mia Rahma; Sormin, Feber (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This study analyses the role of company owners based on the number of shares owned by institutions, the largest shareholder, and foreign owners on tax planning of manufacturing companies from 2014 to 2019. Using STATA on panel data after purposive sampling, this study concludes that institutional owners play a role in encouraging management in tax planning towards aggressive minimisation of tax burden, but foreign owners are known to encourage management in tax planning towards compliance, and concentrated ownership has no significant effect. These results contribute to stakeholders who have an interest in corporate tax procedures and burdens to consider the company's shareholders for their role in tax planning by management. The use of Effective Tax Rate and Penalty (ETRP) as an indicator of tax planning developed in this study shows maximum results so that it can be used in further research.